Acute effects of a dietary non-starch polysaccharide supplement on cognitive performance in healthy middle-aged adults. (February 2015) - Best, Talitha; Howe, Peter; Bryan, Janet; Buckley, Jonathan; Scholey, Andrew
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Certain plant polysaccharides may provide psychological health benefits. The aim of this study was to evaluate whether they can acutely improve mood and cognitive function. Method In a randomized, double-blind, placebo-controlled, between subjects design trial, 73 middle-aged adults consumed 4 g of a proprietary mixture of non-starch polysaccharides (NSPs) (Ambrotose® complex), a rice flour placebo, or a sucrose control. Participants completed testing at baseline and 30 minutes post-consumption. Acute effects of consumption on mood, cognition, and blood glucose were evaluated during mental tests designed to induce mental fatigue. Results Significant improvement in recognition and working memory performance was observed in the group that consumed NSP compared with placebo or sucrose. Improvements in memory performance following NSP intake were independent of changes in blood glucose. Discussion This is the first report of acute behavioural improvement following plant polysaccharide intake in healthy middle-aged adults under conditions of mental fatigue. The findings suggest that certain NSP may enhance memory performance through mechanisms other than elevated blood glucose.